Digital Media Innovation Based on Multimedia Cognitive and Constructivist Theory in a Cultural Context: Encouraging Students' Higher Order Thinking Skills - Siregar, Budi Halomoan; Panjaitan, Asmin; Hasratuddin, Hasratuddin; Kairuddin, Kairuddin; Mulyono, Mulyono; Rahman, Arief Aulia (Universitas Muhammadiyah Mataram, 2024)
The high-order thinking skills of students in Indonesia are classified as low, this is in line with the results of diagnostic tests conducted in class IX junior high school. Thus, it is necessary to develop digital media based on multimedia and constructivist cognitive theory with cultural context as one of the alternative solution. This study aims to (1) develop digital learning media based on constructivist and cognitive multimedia theories with a cultural context that fulfills the categories of validity, practicality and effectiveness; and (2) improve students' high-order thinking skills after using these media in the learning process. The research subjects were 30 students in class IX junior high school and the research objects were digital learning media based on constructivist theory and cognitive multimedia with a cultural context to improve students' high-level thinking skills on the topic of dilation. This is a research design with the Plomp model, which consists of (1) Preliminary research; (2) Prototyping phase; and (3) Assessment phase. The research instruments used were interviews, questionnaires and tests. The results showed that the product developed was included in the very valid, very practical, and effective category, where: (a) classical learning completeness reached 97%; (b) positive response by product users reached 97%; and (c) the N-Gain value was 0.791 in the very high category. Thus, it can be stated that the product meets the quality standard criteria, where the product can be used to improve students' high-level thinking abilities.